Investigating the Characteristics of Knowledge-Related Learning Assignments in Upper Secondary School - Liisa Ilomäki; Minna Lakkala; Hanni Muukkonen; Sami Paavola; Auli Toom (MDPI AG, 2023)
This study reports on whether students have the opportunity to acquire generic competencies when they work with knowledge-related assignments at upper secondary school. We investigated 30 assignments. The data included lesson observations and interviews with teachers. The main categories of teaching practices were theory-based, and the subcategories and the levels of intensity were based on qualitative analysis of the data. The most common categories were Object-orientedness, Epistemic challenge, Process-like emphasis, Intensity of collaboration, Cross-fertilisation, and Information practices. The least common categories were Cross-fertilisation, Process-like emphasis, and Object-orientedness. Cluster analysis produced three groups: Open and challenging assignments with guidance and support (eight cases), Demanding assignments without support (seven cases), and Well-defined, teacher-directed assignments (15 cases). Assignments of the first type support students' knowledge-related competencies the best. The second type of assignment is demanding because students work independently with limited support for challenging assignments. Assignments of the third type were well-structured and teacher-centered assignments.